Towards Understanding the Immigrant Cultural Diversity in the Churches in Canada: A Values-Based Approach in the Participation of Visible Minorities in The United Church of Canada - Smith, Junior Anthony (Université Saint-Paul / Saint Paul University, 2016)
Today, both globalization and immigration have significantly altered the Canadian demographics. Our interactions across borders have become less and less obtrusive both for governments, corporations and individuals. As a result, our cultural interactions no longer require travel to far off places. Technological advances bring these experiences into our living spaces. Furthermore, Canada’s monolithic and predominantly White culture of the 1960s has changed with the arrival of individuals from places other than Europe and the United States. This shift in the cultural dynamics, the ageing cohort particularly among the Roman Catholic and Protestant populations, the decline in the number of young people identifying with these denominations, and the increase in individuals identifying themselves as “no-traditional” faith and “no religion,” have all contributed to a general decline in attendance in the mainline churches. Over this period, The United Church of Canada has recognized the impact of these demographic and social changes. The church has also recognized that in order to become a more welcoming community, it must understand the underlying values of this demographic segment along with its “traditional” membership so as to continue to celebrate the commonality of all cultures, values and traditions while recognizing and finding ways to mitigate the inhibiting consequences of their differences. The objective of this research is to identify and to move towards understanding the core values and traditions within the context of a multicultural, multi-generational, postmodern, and changing church. The study explores whether the similarities and differences between the individual values, and the similarities and differences in spirituality/religiousness between the study groups, provide indicators that will advance the need to become a more intercultural and inclusive church. Furthermore, this research examines the question: How can Scripture inform the church towards the treatment of visible minorities both inside and outside of the church?
Keywords: values; United Church; Schwartz; immigrant; diversity; culture; Canada; Church; model; spirituality; religious; Scripture